KRIMINALISASI HAKIM DAN EKSISTENSI PRINSIP JUDICIAL INDEPENDENCE DALAM BINGKAI NEGARA HUKUM - Muh Risnain (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
Legal policy throught criminalization of judge by the law are abuse of judicial indpence and threat of rule of law principle while regulate by the constitution. And it is shown that quo vadis of criminalization policy when drafting the law. To solve this problem, there are two step, firstly, House of representative and President as state organs who have authority to arrange the law must pay attention principle of judicial indepence and rule of law, second, reorientation of criminal policy. Keywords: Criminalization, Judicial Independence and Rule of Law.